Institutional Leaders' Employment of Flexible Leadership in a Philippine State University - Nordy D. Siason, Jr; Amabel Tangco-Siason (Ali Khorsandi Taskoh, 2023)
This descriptive research investigates the degree of flexible leadership employed by institutional leaders amidst the emerging and anticipated shocks in the context of a higher education institution (HEI) in the Philippines. Eight (8) college deans and 143 faculty members assessed the implementation of flexible leadership in all five (5) campuses. Through a survey, variables of flexible leadership were considered high: building commitment to core ideology; building capable leadership; involvement and empowerment; keeping communication lines open; using reward system to support multiple objectives; and encouraging and exemplifying leadership by examples. Notably, a flexible leader understands the university's objectives, priorities, and strategies (M=4.57), builds and supports its values system (M=4.51), and understands that faculty members are the university's most valuable asset (M=4.50). Through interview protocols and triangulation, there were facets to be focused on like holding regular forums to discuss issues and changes, encouraging an open-door policy to increase access to information, and ensuring that faculty members not only understand what is expected of them but are committed to doing it. Flexible leadership can be nurtured and this implies commitment, credibility, and consistency among institutional leaders to reap more academic successes amidst the challenges faced by an HEI.